2009
DOI: 10.1111/j.1582-4934.2009.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB regulation: the nuclear response

Abstract: Nuclear factor κB (NF-κB) is an inducible transcription factor that tightly regulates the expression of a large cohort of genes. As a key component of the cellular machinery NF-κB is involved in a wide range of biological processes including innate and adaptive immunity, inflammation, cellular stress responses, cell adhesion, apoptosis and proliferation. Appropriate regulation of NF-κB is critical for the proper function and survival of the cell. Aberrant NF-κB activity has now been implicated in the pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
94
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(99 citation statements)
references
References 114 publications
4
94
0
Order By: Relevance
“…Conversely, de phosphorylation of Ser-536 by the phosphatase WIP1 was recently shown to inhibit N F -kB transactivation function (29). The p65 subunit undergoes further posttranslational modifications that include acetylation at residues Lys-122, Lys-218, and Lys-310, mediated by p300/CBP and other proteins with histone acetyl transferase (HAT) activity to enhance p65 transcriptional activity (95). Furthermore, p65 activity can be negatively regulated through SOCS-1-dependent ubiquitination of residues 220 and 335, leading to p65 proteasomal degradation (58,127).…”
Section: An Overview Of Nf-kb Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, de phosphorylation of Ser-536 by the phosphatase WIP1 was recently shown to inhibit N F -kB transactivation function (29). The p65 subunit undergoes further posttranslational modifications that include acetylation at residues Lys-122, Lys-218, and Lys-310, mediated by p300/CBP and other proteins with histone acetyl transferase (HAT) activity to enhance p65 transcriptional activity (95). Furthermore, p65 activity can be negatively regulated through SOCS-1-dependent ubiquitination of residues 220 and 335, leading to p65 proteasomal degradation (58,127).…”
Section: An Overview Of Nf-kb Signalingmentioning
confidence: 99%
“…RelA/p65 (here after referred to as p65) can be phosphorylated on nu merous amino acids including Ser-276, Ser-529, and Ser-536. These modifications are directed by various kinases such as protein kinase A (PKA), mitogen-and stressactivated protein kinase 1 (MSK1), Tank binding kinase 1 (TBK1), and casein kinase 2 (CK2) (19,95,111). Ser-311 is also phosphorylated in vitro directly by the £-isoform of protein kinase C and in vivo through tumor necrosis factor (TNF)-a stimulation (43).…”
Section: An Overview Of Nf-kb Signalingmentioning
confidence: 99%
“…It is well known that NF-κB is one of the most important mediators related to inflammation. The elevated expression of NF-κB is considered to be a fundamental event in many acute and chronic inflammatory disorders [18,19], so significant attention has been focused on the development of anti-inflammatory drugs targeting NF-κB [20]. In this study, we found that the expression of NF-κB p65 markedly increased in pouches of the Ti group compared with those of the PBS group on both day 2 and day 7, while a significant decrease in the expression levels of the protective mediator IκBα was observed in pouches of the Ti group compared with levels in the PBS group.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a possibility that miR-939 can also bind to p65, which merits future studies to verify. Additionally, NF-κB has been linked to a wide variety of signaling mediators such as JNK, AP-1 and MAPK, aside from Bcl-xL [44,45]. It would be important to clarify in the future whether these other factors are also regulated by miR-939 through decoy-like action on NF-κB.…”
Section: Discussionmentioning
confidence: 99%